Effects of breed proportion and components of heterosis for semen traits in a composite cattle breed - Khayatzadeh, N.; Mészáros, G.; Utsunomiya, Y. T. [UNESP]; Schmitz-Hsu, F.; Seefried, F.; Schnyder, U.; Ferenčaković, M.; Garcia, J. F. [UNESP]; Curik, I.; Sölkner, J. (Wiley, 2018)
The aim of this study was to estimate the non-additive genetic effects of the dominance component of heterosis as well as epistatic loss on semen traits in admixed Swiss Fleckvieh, a composite of Simmental (SI) and Red Holstein Friesian (RHF) cattle. Heterosis is the additional gain in productivity or fitness of cross-bred progeny over the mid-purebred parental populations. Intralocus gene interaction usually has a positive effect, while epistatic loss generally reduces productivity or fitness due to lack of evolutionarily established interactions of genes from different breeds. Genotypic data on 38,205 SNP of 818 admixed, as well as 148 RHF and 213 SI bulls as the parental breeds were used to predict breed origin of alleles. The genomewide locus-specific breed ancestries of individuals were used to calculate effects of breed difference as well as the dominance component of heterosis, while proxies for two definitions of epistatic loss were derived from 100,000 random pairs of loci. The average Holstein Friesian ancestry in admixed bulls was estimated 0.82. Results of fitting different linear mixed models showed including the dominance component of heterosis considerably improved the model adequacy for three of the four traits. Inclusion of epistatic loss increased the accuracy of the models only for our new definition of the epistatic effect for two traits, while the other definition was so highly correlated with the dominance component that statistical separation was impossible.
Keywords: breed composition; dominance; epistatic loss; heterosis; semen traits; Swiss Fleckvieh